Unleashing the potential: Enhancing technology adoption and innovation for micro, small and medium-sized enterprises (MSMEs) - Mei Kay Loo; Sridar Ramachandran; Raja Nerina Raja Yusof (Cogent Economics & Finance, 2023)
This study conducts a comprehensive systematic review to gain insights into the challenges of technology adoption and innovation for Malaysian Micro, Small and Medium-sized Enterprises (MSMEs), which play a crucial role in the country's economy. These MSMEs face obstacles, including challenges in adopting technology and a lack of technical efficiency. To address these issues, the study explores prominent technology adoption theories (e.g. TAM, DOI) and organizational theories (e.g. RBV, ST). By addressing these challenges, policymakers can enhance MSMEs' competitiveness through targeted strategies, fostering innovation and effective technology adoption, thus contributing to their growth and resilience in the Malaysian economy.
Keywords: 330; innovation; theories and models; Msmes performance; technology adoption